Dinâmicas e estratégias de reprodução socioeconômica da agricultura familiar na Amazônia brasileira: o caso de Mãe do Rio, Pará - Reis , Cleoson Moura dos (2021)
This research aimed to analyze the dynamics of agriculture and the socioeconomic reproduction strategies of family farming in the municipality of Mãe do Rio - PA, Brazilian Amazon. The theoretical-methodological framework provided by the systemic approach was used for the study of agrarian realities, particularly in the Theory of Agrarian Systems, where the fundamental element is the concept of Agrarian System, whose operationalization allowed unveiling the particularities and characteristics of its origin, evolution and differentiation of agriculture in the Mãe do Rio region – PA. Typology and case study resources were used to understand family farming, how it articulates the livelihoods, the self-controlled resource base, the mobilization of different strategies to ensure its socioeconomic reproduction. In addition to a bibliographic survey, data and secondary information, the field research carried out in the period from December 2020 to February 2021, allowed the application of the survey questionnaire with family farmers in their Agricultural Production Units (UPA) indicated through the typology, as well as informal interviews with key interlocutors, and for the analysis of the collected data, an electronic spreadsheet developed in “Microsoft Excel” was used. As a result, the historical reconstruction of agriculture pointed to the existence of four distinct agrarian systems: the Ancient Indigenous Agrarian System (about 3,500 years before the present (AP) to 1500), the Agrarian System Agroexportador Escravocrata (1500 to 1850), the System Agrário Colonial Agrícola (1850 to 1950), and the Contemporary Agrarian System (1950 to the present day). The social, economic and productive characteristics of family farming allowed adjusting a typology, with the orientation of different strategies and their combinations, of socioeconomic reproduction locally in five social types, namely: Type 1 – Undercapitalized and economically vulnerable family farmer; Type 2 – Capitalized, highly specialized and commodified family farmer; Type 3 – Family farmer focused on self-consumption and dependent on social transfers; Type 4 – Undercapitalized family farmer, dependent on agroextractivism and pluriactivity; and Type 5 – Family farmer in the process of capitalization, diversified and pluriactive. The study concluded that, because of the complex and particularly dynamic agrarian history, the region of the municipality of Mãe do Rio is currently home to a very diverse agriculture, being ubiquitous from shifting practices of slash-and-burn agriculture to the use of modern techniques such as agricultural mechanization and genetic improvement in beef cattle. Social types characterize the diversity of family farming, as well as the complexity of practices and productive strategies used to aim at the socioeconomic reproduction of families, where agricultural income and self-consumption are present in all types identified.